COVID-19: un nuevo reto para la cadena de suministro - Palomino Alonso, Nicole Gloria (2021)
The objective of this article is to identify trends, strategies, actions used against COVID 19 and negative impacts on the supply chain through a literature review and an interview with an expert in the field. At present, the supply chain is known as the set of processes involved in the flow of a product that reaches the final consumer, covering aspects such as planning, storage, distribution, among others; However, this definition has evolved over the years, even more so with the pandemic, its concept is redefined and incorporates new topics, making this research informative, preventive and indicative for the formulation of strategic plans and plans of action through benchmarking. To this end, a thematic introduction and an exhibition of good practices through the state of the art is developed. Likewise, a theoretical base is incorporated in order to guide the reader on the investigation through the most relevant evidence found in articles with similar topics such as supply chain concepts and problems. The results were grouped into topics such as purchasing, storage, distribution, supply and general aspects. Finally, the discussion on the presented findings and the pertinent conclusions is developed